Longe do tronco, perto das grades: a criminalização da capoeira no código penal de 1890 e o controle social na pós-abolição. - Antunes, Maria Eduarda Rodrigues (2022)
The present work analyzes the social control over the black and the economically disadvantaged people in the 19th century, after the abolition of slavery. How the criminalization of capoeira and vagrancy, in the Penal Code of 1890, contributed to perpetuating the stigmatization they already suffered. Based on a specific case, habeas corpus filed in Pernambuco's Justice, in 1895, the forms of application of justice to the accused, who were serving time isolated on the island of Fernando de Noronha, are problematized. We also address related issues raised by the central theme. To reach the result presented in this report, books, dissertations, articles published in specialized magazines and legislation were consulted. Nominal research was also carried out in period newspapers and digital image files. As a final product, the magazine “Conta Outra” was produced. Initially available in PDF, aimed at the lay public, students and people interested in research, each subject addresses a relevant aspect of the topic, with accessible language and dynamic visuals, in color. In the end, it became clear how punishment can be used as a foundation to instrumentalize segregation and manufacture inequalities.